HUBUNGAN PENYIMPANAN VAKSIN DENGAN KERUSAKAN VAKSIN DI PUSKESMAS HELVETIA TAHUN 2015 - Sembiring, Rinawati; Panjaitan, Masriati; Febriyanti, Febriyanti (JURNAL HEALTH REPRODUCTIVE, 2016)
Vaccine is a material use to stimulate the formation of antibodies that include into the body from injection and mouth. Vaccine storage is a way to maintain the condition of the vaccine is not damaged so that the vaccine remains in good condition, thus the quality of the vaccine remains guaranteed One cause of the high rate of incidence of Post Immunization is due to the condition of a vaccine that has been damaged. Based oninformation from coordinator of immunization that Public Health Office of Sibolga said that rarely know the incidence of such damage, because of that Public Health rarely to visits to each health center, it's just that when visits to each health center then it is known. Also based on information from the Coordinator of Immunization, workers already understand how to look at the conditions of temperature vaccine called VVM,but the officer did not see the temperature of the vaccine through the VVM or it can be said officers often neglect the condition VVM vaccine so it is not uncommon damage Vaccine result of exposure to temperatures that do not fit. The purpose of this study was to determine the relationship with the vaccine storage vaccine damage. This study was carried out in health centers throughout the Municipality of Sibolga on July 2015. Thisresearch is a descriptive correlation, using a cross sectional study design. The population is all immunization workers in health centers throughout the all of Sibolga and sample in this research is all of a population of 30 people were taken by using the total population. Data analysis using the chi-square test with a significance value of 0.5%. The results showed that there was a relationship with the vaccine storage of vaccine damage in health centers throughout the all of Sibolga in 2015 with a value of p=0.000